Opioids in Post-stroke Pain: A Systematic Review and Meta-Analysis - Scuteri, Damiana; Mantovani, Elisa; Tamburin, Stefano; Sandrini, Giorgio; Corasaniti, Maria Tiziana; Bagetta, Giacinto; Tonin, Paolo (Frontiers in Pharmacology, 2020)
Background.Post-stroke pain is one of the most common sequelae of stroke, which stands among the leading causes of death and adult-acquired disability worldwide.The role and clinical efficacy of opioids in post-stroke pain syndromes is still debated. Objectives.Due to the important gap in knowledge on the management of post-stroke pain,this systematic review aimed at assessing the efficacy of opioids in post-stroke pain syndromesMethods.A literature search was conducted on databases relevant for medical scientific literature, i.e. PubMed/MEDLINE, Scopus, Web of Science and Cochrane Library databases from databases inception until August 31st, 2020 for clinical trials assessing the effects of opioids and opioids antagonists on pain reduction and pain related symptoms in patients with post-stroke pain syndromes. Studies assessing the effects of other medications (e.g., tricyclic antidepressant, pregabalin) or non - pharmacological management strategies (e.g., neurostimulation techniques) were excluded. The selected studies have been subjected to examination of the risk of bias.Results.The literature search retrieved 83435 results.After duplicates removal, 34285 articles were title and abstract screened.25 full texts were assessed and 8 articles were identified to be eligible for inclusion in the qualitative summary and narrative analysis, of which three were placebo-controlled and two were dose-response.Among placebo-controlled studies, two evaluated the analgesic effect of morphine and one assessed the effects of the opioid antagonist naloxone on patients with central post-stroke pain.With regard to dose-response studies, both were on patients with central post-stroke pain, one assessing the efficacy of levorphanol, and the other on naloxone. Seven out of eight included studies showed an overall slight analgesic effect of opioids, with less consistent effects on other pain-related symptoms (mood, quality of life). Randomized controlled trials were subjected to meta-analysis and rating of the quality of evidence for the two outcomes considered according to GRADE system.Overall results are inconclusive because of the small number of studies and of patients.Conclusions.The limited number of the included studies and their heterogeneity in terms of study design does not support the efficacy of opioids in post-stroke pain and in pain-related outcomes.Large double-blind randomized clinical trials with objective assessment of pain and related symptoms are needed to further investigate this topic.